2018
DOI: 10.1161/jaha.118.009540
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and Contractile Function of Human Right Atrial Tissue in Response to Remote Ischemic Conditioning

Abstract: BackgroundRemote ischemic preconditioning (RIPC) by repeated brief cycles of limb ischemia/reperfusion attenuates myocardial ischemia/reperfusion injury. We aimed to identify a functional parameter reflecting the RIPC‐induced protection in human. Therefore, we measured mitochondrial function in right atrial tissue and contractile function of isolated right atrial trabeculae before and during hypoxia/reoxygenation from patients undergoing coronary artery bypass grafting with RIPC or placebo, respectively.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…It uses human atrial trabeculae isolated from right atrial appendages harvested at the time of cardiac surgery [ 440 ]. The human atrial model has proved to be a unique translational tool, confirming in humans what has been shown in cell models and in vitro/in vivo animal studies [ 253 ].…”
Section: The Human Right Atrial Trabeculae Model Of Simulated Ischemimentioning
confidence: 73%
“…It uses human atrial trabeculae isolated from right atrial appendages harvested at the time of cardiac surgery [ 440 ]. The human atrial model has proved to be a unique translational tool, confirming in humans what has been shown in cell models and in vitro/in vivo animal studies [ 253 ].…”
Section: The Human Right Atrial Trabeculae Model Of Simulated Ischemimentioning
confidence: 73%
“…Our data demonstrate that pre-ischemic administration of DiMAL, mimicking preconditioning, is cardioprotective both in rats and in human cardiac tissue with an efficacy comparable to IPC. Remote IPC, postconditioning, hypothermia and cyclosporine A can induce the same level of cardioprotection as DiMAL 33,34 . The additive effect of hypothermia and DiMAL on infarct size was protective by distinct mechanisms.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have shown that plasma or plasma dialysate from pigs undergoing RIPC not only reduces infarct size and mitochondrial ROS production but also improves ADP-stimulated complex I respiration, ATP production and calcium retention capacity in isolated perfused rat hearts subjected to 30 min of global ischemia followed by 120 min of reperfusion; in addition, these studies have shown that the plasma dialysate increases the viability of mouse cardiomyocytes after hypoxia/reoxygenation 50,51 . A clinical study has demonstrated that RIPC also improves mitochondrial and contractile function in right atrial tissue in patients www.nature.com/scientificreports www.nature.com/scientificreports/ with double-or triple-vessel coronary artery disease 52 . Therefore, mitochondria are fundamental targets for cardioprotective strategies, and conservation of mitochondrial function is the focus of treatments to reduce IRI 53 .…”
Section: Discussionmentioning
confidence: 99%